The influence of the fertilizing system on the petroleum residues biodegradation on a preluvosoil under control polluted - Sabau, N.C.; Sandor, Maria; Domuta, Cornel; Brejea, R.; Domuta, Cristian (Acta Agraria Debreceniensis, 2010)
The paper presents the partial results of researches regarding the agrochemical melioration of soils under control polluted by petroleum residues that took place at the Agricultural and Research and Development Station in Oradea, Bihor County. The experimental device was made out of 1 m2 microparcels, spread out in subdivided parcels, in four repetitions, having tree factors: A - the pollution by crude oil from Suplacu de Barcău, B – the mineral fertilization, and C – the organic fertilization. The experience was set out on a preluvosoil în the year 1993 and the soil was cultivated with millet in the first 3 years and with spring wheat in the last 7 years of research. The researches carried out in Oradea had the objective of establishing the effects of the fertilizing system on the petroleum residue biodegradation on a preluvosoil under control polluted with crude oil from Suplacu de Barcău, Bihor County.